ศีล สมาธิ ปัญญา ในบริบทการปรึกษาเชิงจิตวิทยาแนวพุทธ - แสนอุบล, ดร.ครรชิต (วารสาร ศึกษาศาสตร์ มมร, 2017)
บทความนี้ ผู้เขียนต้องการที่แสดงให้เห็นการปรึกษาเชิงจิตวิทยาแนวพุทธ โดยการใช้กรอบของศีล สมาธิ และปัญญา เป็นพื้นฐานในการให้คำปรึกษา เพื่อต้องการพาคนออกจากภาวะแห่งความมืดมน สันสนหดหู่ เศร้าโศกเสียใจ ซึ่งเป็นความทุกข์ที่เกิดขึ้นกับมนุษย์ในโลกนี้ ให้เข้าสู่ภาวะที่แจ่มใส มีความสุข มั่นคง สงบเย็นกายและใจ เมื่อศึกษาแล้วพบว่า ศีล สมาธิ และปัญญา เป็นกระบวนการดับทุกข์ การจะเกิดขึ้นมีได้นั้น จะต้องผ่านกระบวนการฝึกฝนอบรม ด้วยความอดทนเพื่อให้เกิดการเพิ่มพูนประสบการณ์เป็นองค์ความรู้ของกระบวนการปรึกษา เพื่อเป้าหมายที่จะช่วยให้มนุษย์มีความสุขและเป็นอิสระจากความทุกข์ แต่ทั้งนี้ ก็ต้องอยู่บนพื้นฐานของการนำพุทธธรรมไปปฏิบัติจริง จึงจะถึงเป้าหมายของการปรึกษาเชิงจิตวิทยาแนวพุทธ คือ ความสงบ สะอาด และสว่างในที่สุด Abstract This article aimed to study and explain concepts of The Buddhist Counseling Psychology, including the applying the concepts of Buddhist Doctrines by synthesized on principles and techniques of Buddhist practicing, in order to explore the methods and process of self-training and developing. The study indicated that The Buddhist Counseling Psychology is the way to bring out people who were muddle, depress, sad, angry to be the delight, relaxed, relieved, happy, safe, peaceful life. Therefore, the counseling was on the way of doing Buddhist Meditation which applying principles and a process of Buddhist Doctrine, (Sila: moral practice, Samadhi: mental discipline, Panna: wisdom), for instance, Psychotherapy, Meditate-therapy, and Enlightened-therapy. Moreover, an applying those concepts will help the therapists reducing their desired by keeping practicing on mental control and living an austere life. In the conclusion, the Buddhist Counseling Psychology aims to the therapists realizing and understanding the cause and conditions of things in nature, this will lead them being happy, peaceful and liberated.